2014
DOI: 10.4238/2014.january.21.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bradykinin on renal mesangial cell proliferation and extracellular matrix secretion

Abstract: ABSTRACT. Recent studies have found that bradykinin (BK) plays a role in delaying glomerulosclerosis, although the mechanism of this phenomenon remains unclear. Mesangial cell proliferation (MCP) and extracellular matrix (ECM) secretion are important mechanisms for glomerulosclerosis. This study investigated the impact of BK on the platelet-derived growth factor (PDGF)-induced proliferation of mesangial cells, and evaluated its correlations with the extracellular signal-related kinase (ERK) signaling pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The proliferation of mesangial cells is a common pathological feature of glomerular diseases, including IgA nephropathy and lupus nephritis ( 11 ). For these reasons, numerous studies have investigated the contribution of mesangial cells to the development of glomerulosclerosis ( 15 ). However, these studies have concentrated on cultured cells or animal models of glomerular injury and there have been few studies of human mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of mesangial cells is a common pathological feature of glomerular diseases, including IgA nephropathy and lupus nephritis ( 11 ). For these reasons, numerous studies have investigated the contribution of mesangial cells to the development of glomerulosclerosis ( 15 ). However, these studies have concentrated on cultured cells or animal models of glomerular injury and there have been few studies of human mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nelly Blaes reported that BK inhibits TGF-β-induced collagen production by activating the bradykinin B2 receptor (B2R) [27]. Other studies have found that BK inhibits growth factor-induced cell proliferation and ECM secretion [28]. However, the effects of BK on cultured RPE cell proliferation and the mechanism underlying its effects on TGF-β1 remain unknown.…”
Section: Introductionmentioning
confidence: 99%